2016
DOI: 10.1080/08941939.2016.1240837
|View full text |Cite
|
Sign up to set email alerts
|

Superior Pedicle Mammaplasty without Parenchymal Incisions after Massive Weight Loss

Abstract: This technique gave good breast shape, long-term projection, and upper pole fullness, without parenchymal incisions. It restores breast shape and projection, especially in post-bariatric patients. A similar technique has not been described yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Lateral sutures can be used between the skin flap and the chest wall to better close the dead space and improve the lateral contour, but the skin thickness should be carefully evaluated, in order to avoid quilting sutures [ 8 , 64 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lateral sutures can be used between the skin flap and the chest wall to better close the dead space and improve the lateral contour, but the skin thickness should be carefully evaluated, in order to avoid quilting sutures [ 8 , 64 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, this set of cells and growth factors up‐regulate the ki‐67 pathway in the wound, in order to promote the cellular proliferation 33,35,36 . These evidences suggested that injection of filtered fat graft improves wound healing, but the correlation with pain reduction is less clear 18,19,37‐39 …”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of this cancer is good when detected in an early stage and treated adequately, with risk of death less than 5%, lower than other malignancies [ 14 ]. Despite many years of research, the etiopathogenetic mechanisms responsible for it remain poorly understood [ 1 , 15 , 16 , 17 , 18 , 19 ]. Many researches theorize a role of bacterial biofilm around the implant: this leads to chronic inflammation and, successively, to capsule contracture [ 3 ] and/or BIA-ALCL.…”
Section: Introductionmentioning
confidence: 99%